2002
DOI: 10.1046/j.1463-6409.2002.00074.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of Asia in the origin and diversification of hystricognathous rodents

Abstract: In the absence of a comprehensive pre‐Oligocene fossil record, the origin and early evolution of hystricognathous rodents have long been the subject of much uncertainty. Baluchimyinae (Rodentia) were initially interpreted as a subfamily of the ctenodactyloid Chappatimyidae (sciurognathous), a group considered to be endemic to the Indian subcontinent and to be closely related to hystricognathous rodents. A newly discovered early Oligocene hystricognathous rodent, Bugtimys zafarullahi gen. n. et sp. n., describe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
87
0
10

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(102 citation statements)
references
References 51 publications
5
87
0
10
Order By: Relevance
“…We consider it likely that P. aegyptensis and Waslamys attiai are at least slightly older than the relatively poorly-dated P. algeriensis, because BQ-2 and nearby contemporaneous localities lack any evidence for the presence of the immigrant artiodactyl family Anthracotheriidae, a group that otherwise makes its first appearance in Afro-Arabia at Bir el-Ater. Furthermore, Jaeger et al noted that ''several species of [undescribed] (13) phylogenetic analysis of dental characters found the phiomorph-caviomorph clade to be more closely related to two Oligocene Asian baluchimyine lineages (Bugtimys-Hodsahibia and Lophibaluchia) than to Protophiomys. Their topology implies two independent dispersals of hystricognathous rodents into Afro-Arabia: one from within a paraphyletic ''Baluchimyinae'' that gave rise to Protophiomys, and another that gave rise to either phiomorphs alone or to a phiomorphcaviomorph clade.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We consider it likely that P. aegyptensis and Waslamys attiai are at least slightly older than the relatively poorly-dated P. algeriensis, because BQ-2 and nearby contemporaneous localities lack any evidence for the presence of the immigrant artiodactyl family Anthracotheriidae, a group that otherwise makes its first appearance in Afro-Arabia at Bir el-Ater. Furthermore, Jaeger et al noted that ''several species of [undescribed] (13) phylogenetic analysis of dental characters found the phiomorph-caviomorph clade to be more closely related to two Oligocene Asian baluchimyine lineages (Bugtimys-Hodsahibia and Lophibaluchia) than to Protophiomys. Their topology implies two independent dispersals of hystricognathous rodents into Afro-Arabia: one from within a paraphyletic ''Baluchimyinae'' that gave rise to Protophiomys, and another that gave rise to either phiomorphs alone or to a phiomorphcaviomorph clade.…”
Section: Discussionmentioning
confidence: 99%
“…The discovery of hystricognathous tsaganomyid (10) and ''baluchimyine'' (11)(12)(13) rodents in Paleogene deposits of Asia has been interpreted as supporting an Asian origin for the stem lineage of Hystricognathi (10,13,14), but because early phiomorphs and caviomorphs have strictly Afro-Arabian and South American distributions, respectively, the early biogeographic history of crown Hystricognathi remains a matter of persistent debate. Some have argued that phiomorphs and caviomorphs are likely to have shared a common Afro-Arabian ancestor (15)(16)(17), while others have suggested that the phiomorph-caviomorph split might have occurred in Asia, and that caviomorphs dispersed to South America either through Afro-Arabia or via a southern Gondwanan route (13,18). One critical issue that has hindered understanding of the group's historical biogeography is the phylogenetic position of the family Hystricidae, which has been placed as either the sister group of a phiomorph-caviomorph clade or as the sister group of Caviomorpha, in recent molecular phylogenetic analyses (9,(19)(20)(21).…”
mentioning
confidence: 99%
“…The sudden mid-Cenozoic appearance of caviomorphs in South America's stratigraphic record is perplexing, given the continent's geographic isolation at the time and the "AfricanAsian" distribution of the group's nearest putative relatives, Phiomyidae and Baluchimyinae (Marivaux et al, 2000(Marivaux et al, , 2002Jaeger et al, 2010). The venerable notion of caviomorph monophyly (Wood and Patterson, 1959) has been corroborated repeatedly by molecular analyses (Nedbal et al, 1994;Huchon and Douzery, 2001;Opazo, 2005;Farwick et al, 2006;Poux et al, 2006;Huchon et al, 2007;Blanga-Kanfi et al, 2009;Churakov et al, 2010), but morphological evidence has remained more ambiguous.…”
Section: Introductionmentioning
confidence: 98%
“…An Asian origin for caviomorphs has been proposed on molecular and morphological grounds (Hussain et al, 1978;Flynn et al, 1986;Jaeger, 1989;Huchon and Douzery, 2001). Nevertheless, dispersal between Asia and South America via North America or Australia-Antarctica is contradicted by the lack of early Cenozoic hystricognaths in any of these locations (Hartenberger, 1985;Wood, 1985;Houle, 1999;Marivaux et al, 2002). South America's isolation during most of the Cenozoic produced highly endemic land mammal faunas.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation